2022
DOI: 10.1155/2022/4881494
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practices (KAP) Regarding Meat Safety and Sanitation among Carcass Handlers Operating and Assessment of Bacteriological Quality of Meat Contact Surfaces at the Marrakech Slaughterhouse, Morocco

Abstract: According to the Moroccan Court of Auditors, the meats are prepared in slaughterhouses that do not meet the basic conditions required by Moroccan standards. This survey is being conducted to assess the knowledge, attitudes, and practices of handlers regarding the salubrity and hygiene of meat and to evaluate the bacteriological load of work surfaces in a slaughterhouse located in the Marrakech region. A total of 100 people working at the slaughterhouse participated in the study. The average values concerning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…Therefore, retail butcher shops are difficult to operate compared to large entrepreneurs. This is consistent with the study by Bahir et al (2022), who reported that cost affects standard slaughterhouse compliance. As a result, butchers may not be able to comply with all applicable laws, and some legal rules are difficult to follow.…”
Section: 03 Highsupporting
confidence: 93%
See 3 more Smart Citations
“…Therefore, retail butcher shops are difficult to operate compared to large entrepreneurs. This is consistent with the study by Bahir et al (2022), who reported that cost affects standard slaughterhouse compliance. As a result, butchers may not be able to comply with all applicable laws, and some legal rules are difficult to follow.…”
Section: 03 Highsupporting
confidence: 93%
“…However, butchers at Baan Din Dam, Muang District, Maha Sarakham Province, still need government assistance with regulatory and regulatory measures, which may include knowledge and understanding of proper sanitation practices in slaughterhouses. The results of this study are consistent with studies by Waldman et al (2020) and Bahir et al (2022), which studied knowledge, attitudes, and practices about slaughterhouses. They found that people working in slaughterhouses had a low level of understanding, especially regarding cleanliness and hygiene and making meat safe from pathogens.…”
Section: 03 Highsupporting
confidence: 91%
See 2 more Smart Citations
“…DOI: https://dx.doi.org/10. 54203/scil.2023.wvj12 The current study is a complement to previous research published by the Laboratory of Microbiology and Molecular Biology, Mohammed V University, Rabat, Morocco, providing information on the level of knowledge, attitudes, and practices of workers, as well as on the microbiological situation of the slaughter areas of the municipal slaughterhouses of Marrakech city located in southern Morocco (Bahir et al, 2022). This study aimed to assess the knowledge, attitudes, and practices of food handlers in four Moroccan municipal slaughterhouses in Rabat, Salé, Kenitra, and Meknes, situated in Morocco.…”
Section: Introductionmentioning
confidence: 85%